Investigation of plasma lenses in NSC KIPT - Onishchenko, I.N. (Вопросы атомной науки и техники, 2012)
The results of carried out at NSC KIPT theoretical and experimental studies of focusing electron and ion beams with using plasma lens are presented. Several mechanisms of beam focusing in plasma are considered: plasma compensation of defocusing space charge field of the beam, focusing by electric and magnetic fields of charged current-carrying plasma, ejected from the plasma gun, and focusing by high-frequency wakefield excited in plasma by a sequence of short relativistic electron bunches. Представлены результаты проводимых в ННЦ ХФТИ теоретических и экспериментальных исследований фокусировки электронных и ионных пучков плазменной линзой. Рассмотрены несколько механизмов фокусировки пучков в плазме: плазменная компенсация дефокусирующих полей пространственного заряда пучка, фокусировка электрическими и магнитными полями заряженной токонесущей плазмы, эжектируемой из плазменной пушки, и фокусировка высокочастотными кильватерными полями, возбуждаемыми в плазме последовательностью коротких релятивистских электронных сгустков. Представлені результати проведених у ННЦ ХФТІ теоретичних і експериментальних досліджень фокусування електронних та іонних пучків плазмовою лінзою. Розглянуто декілька механізмів фокусування пучків у плазмі: плазмова компенсація дефокусуючих полів просторового заряду пучка, фокусування електричними і магнітними полями зарядженої струмонесучої плазми, эжектуємої з плазмової пушки, та фокусування високочастотними кільватерними полями, збудженими в плазмі послідовністю коротких релятивістських електронних згустків.